Konwergencja cenowa jako element i wsparcie spójności w Unii Europejskiej - Czaja, Jarosław (Price Convergence as Essential Part of the Cohesion in the European Union, 2006)
In this article I would like to analyze the most important factors influencing the price convergence. It should be underlined that they are fundamental for adoption of common currency in CEEC countries and for current members of euro zone. Because of the latest European extension, problems of labour markets and experiences in fiscal policy on the way to better cohesion I have decided to choose the following factors of price convergence: job mobility; competitiveness; differences in tax level; - differences in inflation level; In conditions of common currency adoption the price convergence process should be still analyzed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 153-160